THE REFUSAL STRATEGIES USED BY THE OLD AND YOUNG FOREMEN IN A BAKERY IN SURABAYA - Eirene Deviani; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2013)
This study is mainly about the refusal strategies used by an old foreman and a young foreman in refusing request permission made by the workers. Specifically, it focuses on the comparison between how the old foreman and the young foreman employed the refusal strategies in refusing request. The findings show that both the old foreman and the young foreman mostly employed indirect strategy